Development and application of a framework for the creation of a food startup in Germany - Cierpiol, Marie-Luise (2017)
The German country carries in its core a traditional and risk-averse character. This is mirrored by the way inhabitants behave, react and work. Industries in Germany follow still traditional processes which often hinder the implementation of novelties and innovations as well as the flexibility towards the market. This has been especially reflected in the case of startups. The German market is very challenging for new businesses as they contain obstacles which can hardly be breached. Simultaneously, startups are very beneficial for a country and its economy. The environment in Germany can also be adapted to the German food industry. The requirements to work with retail stores and wholesalers consist of strict list of conditions as well as expenses that cover listing and marketing fees. These conditions can hardly be met by a startup with its tight financial budgets and fragile business processes. Hence, food startups have to find a way to overcome the traditional processes in order to enter the market. The objective of the thesis is to provide a framework on how a food startup should enter the German market. Finally, the framework is compared to Trinkkost, a new food startup that entered the market in May, 2016. The thesis presents and analyses five German food startups which have entered the German food market, so far, very successfully. The chosen startups are Fritz Kola, Just Spices, True Fruits, Hafervoll and MyMuesli. These startups present best examples on what kind of product a startup should launch on the German market, how a startup can establish their own distribution channels, how marketing activities can be carried out with a tight budget and how or if a startup needs external financial capital to survive and grow on the market. These results combined with an analysis on the German startup environment as well as on the German perception on food leads to the development of a food startup framework. Finally, the food startup Trinkkost is compared with the food startup framework.